Grafiek : Peter Stuyvesant Grafiek-collectie. (Amsterdam : Peter Stuyvesant Stichting)
Adami, Valerio ; Alechinsky, Pierre ; Baj, Enrico ; Boezem, Marinus ; Bogart, Bram ; Corneille ; van Elk, Ger ; Folon, Jean-Michel ; Franse, Kees ; Henneman, Jeroen ; Kitaj, R.B. ; Lataster, Ger ; Lucassen, Reinier ; Maeyer, Marcel ; Morellet, François ; Raveel, Roger ; Spermon, Kees ; Struycken, Peter ; Tilson, Joe ; Westerik, Co
boek